Psychological characteristics and traits in male handball players - optimism, athlete engagement and mental energy - Sindik, J.; Cuk, A.-M. B. (Sport Scientific and Practical Aspects - International Scientific Journal of Kinesiology, 2016)
The main goal of the research is to determine the differences in certain dimensions in the battery of the psychological questionnaires within Multidimensional Scale of Sports` Psychological Talents (MSSPT) in male handball players, according to their club, age group, winning medals and membership in junior national team. Second goal was to determine the profiles of male handball players in all examined psychological characteristics in MSSPT. The purposeful sample of 127 male handball players was examined, members of the teams Prvo plinarsko društvo, Metalac (Zagreb) and Zamet (Rijeka). In this study, three instruments from the battery MSSPT are used: Mental Energy Scale (MES), Athletic Engagement Scale (AES) and Optimism Scale (OS). The results revealed that the most significant differences are found in dimensions of MSSPT between the players of different age groups, while no differences are found according to winning medals in junior state championship, or according to the membership in the junior national team. K-means clustering revealed two profiles of male handball players. In the first cluster are older players with higher means in Self-esteem and Energy as strength while making errors, while in the second cluster are grouped younger players with higher means in all other psychological characteristics.